Comparative Study on the Interaction Between Bovine Serum Albumin and Different Chlorophenols by Spectroscopic Approach - Chen, Yan; Zhou, Pei-Jiang; Liu, Qiong-Yu (Asian Journal of Chemistry, 2011)
The interaction of 4-chlorophenol (4-CP), 2,4-dichlorophenol (2,4-DCP) and pentachlorophenol (PCP), with bovine serum albumin (BSA) was investigated by means of fluorescence spectrometry under simulative physiological conditions. It was found that the intrinsic fluorescence of BSA was quenched uniformly at low PCP concentration or higher 2,4-DCP concentration, while the fluorescence quench of BSA was not observed with the addition of 4-CP. The fluorescence data analysis indicated that PCP and 2,4-DCP bind strongly to BSA by complex formation and the association constants determined by static quenching equation were calculated to be 3.44 × 105 and 1.82 × 104 L mol-1 at 298 K for PCP-BSA and 2,4-DCP-BSA interaction, respectively. The binding affinity order of the three chlorophenols is PCP > 2,4-DCP > 4-CP. The thermodynamic calculation implied that hydrophobic interaction and electrostatic interaction involved in the interaction process. Conformation investigation results confirmed BSA is predominantly a-helical although the microenvironment of BSA was partly changed with the addition of PCP or 2,4-DCP.